1989
DOI: 10.1002/j.1556-6676.1989.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

School and Rehabilitation Counselor Preparation: Meeting the Needs of Individuals With Disabilities

Abstract: In preparing students to work with individuals with disabilities, school and rehabilitation counselor educators face a number of challenges. Highlighting the major changes that have occurred in the 10 years following Hosie's (1979) recommendations for counselor preparation, this article suggests many competencies that are required to meet these challenges and describes how they can be integrated within the applicable accreditation guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Finally, there is a critical need for interdisciplinary collaboration. Hosie, Patterson, and Hollingsworth (1989) suggested that "no one individual or profession can meet the multiple needs of individuals with disabilities" (p. 172). Collaboration and networking with other agencies (Lowenthal & Anderson, 1980-81) will maximize the delivery of scarce resources to a group of individuals who are doubly disabled.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there is a critical need for interdisciplinary collaboration. Hosie, Patterson, and Hollingsworth (1989) suggested that "no one individual or profession can meet the multiple needs of individuals with disabilities" (p. 172). Collaboration and networking with other agencies (Lowenthal & Anderson, 1980-81) will maximize the delivery of scarce resources to a group of individuals who are doubly disabled.…”
Section: Resultsmentioning
confidence: 99%
“…The core counseling courses found in school counselor preparation programs provide a strong foundation and knowledge base for counseling ES. However, some researchers have suggested that counselors who work with these students may need additional knowledge and skills (Hosie, Patterson, & Hollingsworth, 1989;West, 1992). These include (a) information on the characteristics of disabling conditions; (b) how these conditions affect students' physical, social, psychological, and cognitive development; (c) the implications of federal and state laws on the education and counseling services provided in the schools; (d) diagnostic and placement criteria; and (e) methods of modifying interventions to meet specific individual needs.…”
Section: The Role Of Counselors With Esmentioning
confidence: 99%
“…These include (a) information on the characteristics of disabling conditions; (b) how these conditions affect students' physical, social, psychological, and cognitive development; (c) the implications of federal and state laws on the education and counseling services provided in the schools; (d) diagnostic and placement criteria; and (e) methods of modifying interventions to meet specific individual needs. Hosie et al (1989) recommended that school counseling curricula include topics in courses on types of disabilities; range of services for individuals with disabilities; ethnic, cultural, and language issues; family issues; asststtve devices and technology; ethics; and collaboration.…”
Section: The Role Of Counselors With Esmentioning
confidence: 99%
See 1 more Smart Citation
“…Or does the primary blame lie with guidance personnel themselves, who often acquiesce to clerical or quasiadministrative roles instead of insisting on tasks consistent with their training? It is probable that much of the reluctance of counselors to become involved with students with disabilities stems from the fact that most counselor education training programs have inadequately prepared counselors to deal with students who may have special needs (Hosie, Patterson, & Hollingsworth, 1989). In reality, it does not matter who is most "at fault."…”
Section: Problematic Areas In Counseling Persons With Disabilitiesmentioning
confidence: 99%